E-Government Quality: Responding to Needs in Public Policy - Restha, I Nyoman Triyadi; Darma, Gede Sri (Universitas Merdeka Malang, 2025)
This study aims to determine the implementation of e-Government quality in public policy at the Denpasar City Population and Civil Registration Office. The Taringdukcapil application is an effort to develop government administration by utilizing information technology with the aim of improving public services. Of course, in this case, e-Government really needs good accessibility in providing services to the public. e-Government greatly facilitates the government in interacting with the public in an accountable, efficient, transparent and timely manner. The method used in this study is a qualitative descriptive method. Data were collected through documentation, observation and interviews at the Denpasar Population and Civil Registration Office. The results of the study show that the character and condition of society are increasingly dynamic, seen from the increasing level of public education, therefore people in a country are increasingly aware and know the various rights and obligations they have. So in this case, the government as the main gateway that provides public services and determines public policy must always be able to adapt to the development of society itself by making various efforts to improve the quality of service to the public by utilizing technology, for example, so in this case e-government quality is able to answer the needs in public policy.